The microbiota–microglia axis in central nervous system disorders - Mossad, Omar (Brain Pathol, 2020)
The innate immune system in the central nervous system (CNS) is mainly represented by specialized tissue‐resident macrophages, called microglia. In the past years, various species‐, host‐ and tissue‐specific as well as environmental factors were recognized that essentially affect microglial properties and functions in the healthy and diseased brain. Host microbiota are mostly residing in the gut and contribute to microglial activation states, for example, via short‐chain fatty acids (SCFAs) or aryl hydrocarbon receptor (AhR) ligands. Thereby, the gut microorganisms are deemed to influence numerous CNS diseases mediated by microglia. In this review, we summarize recent findings of the interaction between the host microbiota and the CNS in health and disease, where we specifically highlight the resident gut microbiota as a crucial environmental factor for microglial function as what we coin “the microbiota‐microglia axis.”